Costly external financing, investment timing, and investment–cash flow sensitivity - Lyandres, Evgeny (Journal of Corporate Finance, 2007)
This paper examines the effects of costly external financing on the optimal timing of a firm's investment. By altering the optimal investment timing, costly financing affects current investment and the sensitivity of investment to internal cash flow. Importantly, the relation between the cost of external funds and investment–cash flow sensitivity is non-monotonic. Investment–cash flow sensitivity is decreasing in the cost of external financing when it is relatively low and is increasing in the financing cost when it is high. Empirical tests examining investment–cash flow sensitivities within groups of firms classified by proxies for their costs of external funds provide evidence consistent with the model. The model and the empirical results complement recent studies by Cleary, Povel and Raith [Cleary, S., Povel, P. and Raith, M., 2007. The U-shaped investment curve: theory and evidence, Journal of Financial and Quantitative Analysis 42, 1–39.] and Almeida and Campello [Almeida, H. and Campello, M., in press, Financial constraints, asset tangibility and corporate investment, Review of Financial Studies.] that show a non-monotonic relation between firms' investment and the availability of internal funds.